DOES MOTOR CONTROL EXERCISE DECREASES LUMBAR PAIN, IMPROVES MUSCLE ACTIVITY AND REGIONAL FUNCTION IN INDIVIDUALS WITH ACUTE AND SUB ACUTE NON-SPECIFIC LOW BACK PAIN (International Journal of Physiotherapy, 2019)
Background: Non-specific low back pain (LBP) is defined as LBP that poses signs and symptoms which cannot be related to a recognizable cause, and Motor Control Exercise (MCE) usually is the choice of treatment for conditioning lumbar muscles for chronic LBP group. Limited information is available regarding their clinical application for participants with acute and sub-acute LBP. Hence, the main aim of this study is to find out this clinical utility.Methods: A quasi-experimental study with 30 participants of less than six weeks and twelve weeks duration of LBP were included in the study and are divided into an experimental and control group. Pain intensity using numeric pain rating scale (NPRS), lumbar range using modified Schober’s test, muscle function using surface electromyography (EMG) and functional disability using Roland Morris Disability Questionnaire (RMDQ) were recorded pre and post-treatment. The experimental group received lumbar MCE with general exercises and the control group received only general low back exercises aiming to improve lumbar range and muscle efficiency for six-session spread over three weeks duration along with therapy for pain reduction.Results: Subjects in both experimental & control groups had significant improvement in pain (p